Anorexia nervosa - tend the new way of life. Attempt to analyze the current data in this age group - Joanna Siminska; Piotr Porzych; Iwona Głowacka-Mrotek; Joanna Stocka; Krystyna Nowacka; Magdalena Hagner-Derengowska; Wojciech Hagner (Kazimierz Wielki University, 2017)
At the turn of the last few years, a sharp Increase in the number of people suffering from eating disorders That undoubtedly lead or can lead to the destruction of the body is noticeable. These disorders are very often the cause of irreversible mental and physical changes, sometimes even leading to death in extreme cases. The issue of eating disorders, and in Particular the anorexia nervosa occurring most amazing Affects younger age groups. Early observation of the first symptoms and proper diagnosis gives the Possibility of a full recovery. It should also be borne in mind That These disorders are related both to the prevailing socio-cultural changes, sometimes inefficiencies in support structures, as well as to the current year's threatening Increase in the pace of life. Both specific and non-specific eating disorders belong to the group of diseases Whose aetiology, diagnosis and treatment have not been clearly defined so far. However, it should be taken into account That eating disorders are of a chronic nature, so small That they change the clinical picture during the course of the disease, permeating each other.